A Cognitive Semantics analysis of David Goggins’ idea of “transforming” mindset - Drogosz, Anna (Papers in Linguistics, 2023)
The objective of the paper is an analysis of how David Goggins describes his life in his book Can’t Hurt Me. The analysis was conducted within the methodological framework of the Conceptual Metaphor Theory and Blending Theory. It has been established that the metaphors life is a journey and aspects of the self are individuals at war provide coherence to the story of his life, while conceptual blends are a mental tool used to reframe a situation and himself. As a result of implementing those blends in his thinking, David Goggins has developed a mindset that allowed him to transform from a broken teenager to “the strongest man alive”. This case study reveals how specific conceptual blends may impact not only cognition and language in general, as is argued in Cognitive Semantics, but also one’s emotional state, and consequently one’s physical performance.